Molecular simulations of amyloid beta assemblies. Issue 1 (1st January 2020) - Grasso, Gianvito; Danani, Andrea
ABSTRACT: Several neurodegenerative disorders arise from the abnormal protein aggregation in the nervous tissue leading tointracellular inclusions or extracellular aggregates in specific brain areas. In case of Alzheimer Disease, the accumulation of the Amyloid Beta peptide in the brain is proposed to be an early important event in the pathogenesis. Despite significant research efforts in this field, the molecular mechanisms of protein misfolding and aggregation remain somewhat unrevealed.Within this framework,  computer simulations represent a powerful tool able to connect macroscopic experimental findings to nanoscale molecular events.However, from the computational point of view, insufficient sampling often limits the ability of computer simulations to fully address this point. One of the main challenges of MD simulations is the ability to sample experimentally relevant millisecond to second timescales.The present review describes the applications of molecular dynamics techniques to elucidate the conformational states and the aggregation pathway of the Amyloid Beta peptide responsible for AD. Moreover, the computational studies focused on the impact of Amyloid Beta assemblies on cell membranes will be also described. Finally, the interaction mechanisms between promising small molecules and Amyloid Beta assemblies will be discussed within the field of designing new efficient drugs against neurodegenerative disorders. Abbreviations: AD: Alzheimer disease; AB: amyloid beta; ABOs: amyloid beta oligomers; MD: molecular dynamics GRAPHICAL ABSTRACT: uf0001